Ten years a nomad : a traveler's journey home - Kepnes, Matt (St. Martin's Press, 2019)
New York Times bestselling author of How to Travel the World on $50 a Day, Matthew Kepnes knows what it feels like to get the travel bug. After meeting some travelers on a trip to Thailand in 2005, he realized that living life meant more than simply meeting society's traditional milestones, such as buying a car, paying a mortgage, and moving up the career ladder. Inspired by them, he set off for a year-long trip around the world before he started his career. He finally came home after ten years. Over 500,000 miles, 1,000 hostels, and 90 different countries later, Matt has compiled his favorite stories, experiences, and insights into this travel manifesto. Filled with the color and perspective that only hindsight and self-reflection can offer, these stories get to the real questions at the heart of wanderlust. Travel questions that transcend the basic "how-to," and plumb the depths of what drives us to travel <U+2015> and what extended travel around the world can teach us about life, ourselves, and our place in the world. Ten Years a Nomad is for travel junkies, the travel-curious, and anyone interested in what you can learn about the world when you don<U+2019>t have a cable bill for a decade or spend a month not wearing shoes living on the beach in Thailand.